The Influence of Choice of Study Program Concentration in Undergraduate Management and Self-Efficacy on the Study Period of 2020 Students of Undergraduate Management, FEB, Riau University - Perdana Josua; Susi Hendriani; Rahmat Junaidi (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to empirically prove the influence of Concentration Choice and Self-Efficacy on Study Duration. The research was conducted in the Management Department of the Faculty of Economics and Business at Riau University and used data obtained from the distribution of questionnaires to 172 students as respondents. The sampling method in determining respondents for this study uses the proportionate stratified random sampling technique. (teknik sampling berstrata). This study uses statistical data analysis methods employing SPSS version 27. The research results indicate that 1) The choice of concentration had a positive and significant effect on the student's study period, 2) Self-efficacy had a positive and significant effect on the student's study period, 3) The choice of concentration and self-efficacy have a positive and significant effect on student study period. This means that the influence of these factors interacts with each other, where the choice of concentration and high self-efficacy will have an impact on accelerating a good study period as well.